Efficiency and bandwidth improvement of integrated acousto-optic modulators using dielectric acoustic reflectors - Huilong Liu; Jiying Huang; Jiantao Jiang; Hongyi Huang; Huipeng Chen; Chengyu Chen; Haiwei La; Huan Li; Xiaochun Xu; Yuping Chen; Zhaohui Li; Lei Wan (APL Photonics)
Manipulation and control of traveling surface acoustic waves (SAWs) are critical to the realization of high-performance integrated acousto-optic modulators (AOMs). In this paper, we present the chalcogenide glass (ChG) acoustic reflector-loaded thin-film lithium niobate (TFLN) Mach–Zehnder interferometer (MZI) AOMs with single-arm and single-finger configurations based on the forming mechanism of the acoustic standing wave. Through the engineering of dielectric acoustic reflectors, threefold modulation efficiency improvement is achieved for the TFLN MZI AOM with X–Z orientation, while twofold bandwidth extension is demonstrated for the counterpart with X–30°Y orientation. Propagation loss of the Rayleigh SAW around 0.85 GHz and the reflection coefficient of ChG acoustic grating are measured to be 3.04 dB/mm and 0.34, respectively. Introduction of dielectric acoustic reflectors opens a new pathway to the study of efficient and wideband acousto-optic interaction devices.